2016
DOI: 10.1371/journal.pone.0165486
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid Orchestrates Anti-Oxidative Properties of Danggui Buxue Tang, an Ancient Herbal Decoction: Elucidation by Chemical Knock-Out Approach

Abstract: Ferulic acid, a phenolic acid derived mainly from a Chinese herb Angelica Sinensis Radix (ASR), was reported to reduce the formation of free radicals. Danggui Buxue Tang (DBT), a herbal decoction composing of Astragali Radix (AR) and ASR, has been utilized for more than 800 years in China having known anti-oxidative property. Ferulic acid is a major active ingredient in DBT; however, the role of ferulic acid within the herbal mixture has not been resolved. In order to elucidate the function of ferulic acid wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
(52 reference statements)
1
15
1
Order By: Relevance
“…Steroid hormone, especially estrogen, is well-known for ERT in the treatment of osteoporosis ( Choi et al, 2011 ). The side effects of ERT have been reported to increase the risk of developing breast cancer ( Gong et al, 2016 ). Phytoestrogens are now popular for patients with better safety.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Steroid hormone, especially estrogen, is well-known for ERT in the treatment of osteoporosis ( Choi et al, 2011 ). The side effects of ERT have been reported to increase the risk of developing breast cancer ( Gong et al, 2016 ). Phytoestrogens are now popular for patients with better safety.…”
Section: Discussionmentioning
confidence: 99%
“…To prepare DBT Δcal and DBT Δfa , a Dikma, Diamonsil C18 column (10.0 mm × 250 mm, 5 μm) was used to deplete calycosin or ferulic acid from DBT. The depletion methods and conditions were described previously ( Gong et al, 2015 , 2016 ). The authentications of DBT Δcal and DBT Δfa were revealed by LC–MS/MS ( Gong et al, 2015 , 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferulic acid (FA) is a hydroxycinnamic acid found in plant cells, and may protect cell integrity by catalyzing formation of phenoxy radicals . FA is believed to be an active ingredient of Chinese herbal medicine Angelica Sinensis Radix , and its derivatives have been widely applied food, and medicine . Particularly interesting to our current study, FA was consistently reported to induce expression of VEGF in HUVECs .…”
Section: Introductionmentioning
confidence: 53%